Synthesis and characterization of magnetite-based nanocomposites and its evaluation using a Zebrafish Model (2023)
Toxicity tests on environmental ecosystems involving animal models are interesting because these can be used to determine the safety of a chemical. With the increasing use of nanoparticles for different purposes and their possible entry into the environment, there are safety concerns for natural ecosystems and human environments. Many studies have shown that nanoparticles have potential applications. Still, it has also been shown that they can become toxic depending on their specific properties when they come into contact with drinking water or the food chain. Magnetite (Fe3O4) is an iron oxide with unique physical and chemical properties and has found various applications, from drug delivery agents to water remediation. Due to its properties, its use has intensified and has been used as a vehicle for removing contaminants in water such as heavy metals, drugs, and organic. Although its use has demonstrated effectiveness, its environmental implications are unknown. Therefore, since the effects of its use in aquatic ecosystems are not yet known, it is necessary to evaluate its toxicity impact on aquatic ecosystems. For this reason, it is necessary to find a way to evaluate its impact on these ecosystems, and it is here that the zebrafish model appears. Zebrafish has characteristics that allow it to comply with the fundamental principle of animal research known as the 3Rs (i.e., replacement, reduction, and refinement), which is also the model recommended by the Organisation for Economic Co-operation and Development (OECD) for the evaluation of environmental toxicity because it responds to environmental variations. This doctoral thesis work was addressed by evaluating the possible toxicological impacts on the morphology, survival, behavior, reproduction, and bioaccumulation of zebrafish embryos, larvae, and adult animals subjected to treatments with magnetite-based nanocomposites designed for wastewater treatment. As well as determined a safe use after its application as a water remediation agent, based on toxicity assessment concentrations. Our results indicate that magnetite-based nanocomposites, designed for removing contaminants in wastewater and evaluated using the zebrafish model, exhibit no toxic effects on the measured parameters. At the tested concentrations, we were unable to determine the median lethal dose over the duration of the test. Exposure to magnetite-based nanocomposites may lead to increased accumulation levels in the chorion of embryos; however, no adverse effects were observed on the hatching and survival rates of the animals. Furthermore, at the end of the treatment period in embryos or larvae, animal survival remained consistently above 70% at all concentrations tested. This suggests that the nanocomposites studied in this thesis are non-toxic and can be safely used for their intended purposes. No effects were observed that alter the normal development of the animals throughout their life cycle, even at concentrations higher than those recommended by the OECD. Importantly, this thesis presents the first post-treatment reproduction study for zebrafish. These animals were treated during embryonic and larval stages at a concentration ten times higher than that recommended by the OECD. The reproductive capacity of zebrafish was evaluated at two different ages, and the results were highly favorable in terms of hatching and survival of the animals. These findings indicate that magnetite-based nanocomposites do not have long-term toxic effects affecting zebrafish reproductive cycles. We also assessed the adsorption capacity of these nanocomposites for cadmium in aqueous solution and compared them with commercial aluminum oxide spheres. The results demonstrated that the magnetite-based nanocomposites exhibited higher cadmium removal rates compared to aluminum oxide spheres. Furthermore, we successfully recovered the nanocomposites from aqueous media after the cadmium removal studies, ensuring that no significant concentration was left in the environment. In summary, the magnetite-based nanocomposites evaluated in this thesis using the zebrafish model displayed no toxicity in all tested parameters and can be effectively utilized for pollutant removal in wastewater.